The Effectiveness of the Ider-Ider Learning Model Based on Javanese Local Wisdom on Humanistic Literacy of Elementary School Students: Efektivitas Model Pembelajaran Ider-Ider Berbasis Kearifan Lokal Jawa Terhadap Literasi Humanistik Siswa Sekolah Dasar - Puspita, Ari Metalin Ika; Saud, Udin Syaefudin; Damaianti, Vismaia S; Mulyati, Yeti (Universitas Muhammadiyah Sidoarjo, 2021)
The purpose of this study is to determine the effectiveness of the ider-ider learning model based on Javanese local wisdom on humanistic literacy. The research method in this research is quantitative method, while the research design uses Quasi Experimental Design. The data collection technique in this study is to use a questionnaire sheet. Data analysis in this study used a comparative test. the results of the comparison test with the Wilcoxon formula obtained a significance value of 0.001 (<0.05). These results indicate that there is a difference between humanistic literacy before and after the application of the Ider-Ider Learning Model Based on Local Wisdom. This model will be able to provide understanding to students about the value of togetherness or humanism. Based on the results of the study showed that the ider-ider learning model based on Javanese local wisdom was effective in improving the humanistic literacy of elementary school students.